The argumentative Indian : writings on Indian history, culture and identity - Sen, Amartya, 1933- (London : Penguin Books, 2005)
India is a country with many distinct traditions, widely divergent customs, vastly different convictions, and a veritable feast of viewpoints. In The Argumentative Indian, Amartya Sen draws on a lifetime study of his country's history and culture to suggest the ways we must understand India today in the light of its rich, long argumentative tradition. The millenia-old texts and interpretations of Hindu, Buddhist, Jain, Muslim, agnostic, and atheistic Indian thought demonstrate, Sen reminds us, ancient and well-respected rules for conducting debates and disputations, and for appreciating not only the richness of India's diversity but its need for toleration. Though Westerners have often perceived India as a place of endless spirituality and unreasoning mysticism, he underlines its long tradition of skepticism and reasoning, not to mention its secular contributions to mathematics, astronomy, linguistics, medicine, and political economy.
The argumentative Indian -- Inequality, instability, and voice -- India: large and small -- The diaspora and the world -- Tagore and his India -- Our culture--their culture -- Indian traditions and the Western imagination -- China and India -- Tryst with destiny -- Class in India -- Women and men -- India and the bomb -- The reach of reason -- Secularism and its discontents -- India through its calendars -- The Indian identity.
Includes bibliographical references and index.
Keywords: India -- Culture; India -- History; India -- Civilization